Analysis and design of a power supply - Zhou, Jing (Nanyang Technological University, 2023)
The objective of this final year project is to analyse and design a power supply that meets the requirements of a specific application. The project involved a thorough study of the principles and concepts of power circuit design, includes transformer design, rectification, filtering, and voltage regulation. The analysis was carried out using simulation software, and the design was implemented on a printed circuit board. The project resulted in the successful design and implementation of a power supply that meets the requirements of the application. The power supply was tested and found to have a high efficiency and low ripple voltage, which ensures stable and reliable operation of the application. The project also demonstrated the importance of careful analysis and design in achieving optimal performance and reliability of power supply systems. Overall, this final year project provided a valuable learning experience in the area of power supply design, and the knowledge and skills gained can be applied in a wide range of engineering applications.